2005
DOI: 10.1007/s11213-005-4816-7
|View full text |Cite
|
Sign up to set email alerts
|

Soft System Dynamics Methodology (SSDM): Combining Soft Systems Methodology (SSM) and System Dynamics (SD)

Abstract: Soft System Dynamics Methodology (SSDM), a systemic methodology product of the combination of two widely used systems-based methodologies from two different systems thinking paradigms, Systems Dynamics (SD) and Soft Systems Methodology (SSM), is presented. The paper argues that by combining some of SD and SSM stages, within the intellectual framework proposed by SSDM, a methodology developed by one of the authors 1 much can be gained in a systemic intervention to tackle complex social problematic situations. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 26 publications
0
29
0
1
Order By: Relevance
“…Various combinations of SSM and SD have been used previously in other fields of enquiry (Maani and Cavana 2007;Rodriguez-Ulloa and Paucar-Caceres 2005), but have had a tendency to use SD methodology as the primary focus, with enhancements from SSM. In this paper, SSM is viewed as the primary focus, enhanced with aspects of SD.…”
Section: Proposed Hybrid Methodological Approach To Scc Infrastructurmentioning
confidence: 99%
“…Various combinations of SSM and SD have been used previously in other fields of enquiry (Maani and Cavana 2007;Rodriguez-Ulloa and Paucar-Caceres 2005), but have had a tendency to use SD methodology as the primary focus, with enhancements from SSM. In this paper, SSM is viewed as the primary focus, enhanced with aspects of SD.…”
Section: Proposed Hybrid Methodological Approach To Scc Infrastructurmentioning
confidence: 99%
“…The most prominent example of this are the combinations of SD with cognitive mapping (Eden, 1994;Ackermann et al, 1997;Stotz and Größler, 2007), soft systems methodology (Lane and Oliva, 1994;Rodriguez-Ulloa and Paucar-Caceres, 2004;, cybernetics (Schwaninger et al, 2004;Schwaninger and Pérez Ríos, 2008), and multicriteria analysis (Brans et al, 1998;Santos et al, 2002;Pruyt, 2007). All of these demonstrate the power and utility of a multimethodological approach.…”
Section: Introductionmentioning
confidence: 99%
“…They believed that "complexity" became the major issue, because it is complex enough at the practical level to mix methods, and to take into consideration issues at the paradigm level would require extensive effort. Nevertheless, they found that the use of mixed methodologies, in a practical sense, developed significantly over the period (Howick and Ackermann, 2011) As mentioned in Section 3.3.2.5, SD has strengths in providing rigorous dynamic models but is lacking in its capability to overcome multiple clients' perspectives (Lane & Oliva 1998;Jackson 2002;Rodriguez-Ulloa & Paucar-Caceres 2005). Efforts to reduce the limitation of SD methodology in dealing with multiple clients' perspectives and interests have been made by Vennix (1999).…”
Section: Combining the Methodologymentioning
confidence: 99%
“…Forrester (1961) pointed out that problem identification is the important step in SD methodology; however he did not provide sufficient techniques that can be used to fully grasp the problem (Lane & Oliva 1998;Rodriguez-Ulloa & Paucar-Caceres 2005). The rationale behind this concern relates to the common view that SD practitioners tend to give more effort to developing and validating a model which represents real world phenomena than to examining whether the ''problem'' being analysed is really ''the problem'' that needs to be analysed.…”
Section: Strength and Limitation Of System Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation